The image of kinaidos in Plato’s Gorgias - Freitas, Luiz Eduardo (Revista Archai, 2018)
In the final part of Plato’s Gorgias, Socrates uses an example in order to shame Callicles and thereby confront his hedonistic position. The term kinaidos can embarrass translators, interpreters and contemporary readers of the dialogue - some Brazilian editions use translations such as “devasso” and even “veado”. Socrates suggests that if we accept the identification between good and pleasure we should admit the life of the kinaidos as a happy one. But what exactly is the life of the kinaidos? Why cannot it be an example of a happy life? Although this image is abandoned quickly, this socratic argumentative device is decisive for the development of the discussion in the Gorgias. So until these questions are adequately answered, Socrates’ argument will remain partially unintelligible. I start this article trying to demonstrate the importance of the kinaidos as the culminating example in an imagetic refutative process initiated by Socrates. Then I analyze the state of the question and demonstrate why studies of the level of importance of Charles Kahn, Kenneth Dover and John Winkler have not been able to cover all aspects of the meaning of this specific image in the Gorgias. Finally, I try to propose an interpretation according to which the mention of the kinaidos would be a Platonic response to a greek anti-intellectualist thesis, like the one present in Euripides’ Antiope. This response has a crucial role in Plato’s project to legitimize and specify philosophy against the practice of rhetoric.